Targeting type-2 metabotropic glutamate receptors to protect vulnerable hippocampal neurons against ischemic damage. Issue 1 (December 2015) - Motolese, Marta; Mastroiacovo, Federica; Cannella, Milena; Bucci, Domenico; Gaglione, Anderson; Riozzi, Barbara; Lütjens, Robert; Poli, Sonia; Celanire, Sylvain; Bruno, Valeria; Battaglia, Giuseppe; Nicoletti, Ferdinando
Abstract Background To examine whether metabotropic glutamate (mGlu) receptors have any role in mechanisms that shape neuronal vulnerability to ischemic damage, we used the 4-vessel occlusion (4-VO) model of transient global ischemia in rats. 4-VO in rats causes a selective death of pyramidal neurons in the hippocampal CA1 region, leaving neurons of the CA3 region relatively spared. We wondered whether changes in the expression of individual mGlu receptor subtypes selectively occur in the vulnerable CA1 region during the development of ischemic damage, and whether post-ischemic treatment with drugs targeting the selected receptor(s) affords neuroprotection. Results We found that 4-VO caused significantly reduction in the transcript of mGlu2 receptors in the CA1 region at times that preceded the anatomical evidence of neuronal death. Down-regulation of mGlu2 receptors was associated with reduced H3 histone acetylation at the Grm2 promoter. The transcripts of other mGlu receptor subtypes were unchanged in the CA1 region of 4-VO rats. Ischemia did not cause changes in mGlu2 receptor mRNA levels in the resistant CA3 region, which, interestingly, were lower than in the CA1 region. Targeting the mGlu2 receptors with selective pharmacologic ligands had profound effects on ishemic neuronal damage. Post-ischemic oral treatment with the selective mGlu2 receptor NAM (negative allosteric modulator), ADX92639 (30 mg/kg), was highly protective against ischemic neuronal death. In contrast, s.c. administration of the mGlu2 receptor enhancer, LY487379 (30 mg/kg), amplified neuronal damage in the CA1 region and extended the damage to the CA3 region. Conclusion These findings suggest that the mGlu2 receptor is an important player in mechanisms regulating neuronal vulnerability to ischemic damage, and that mGlu2 receptor NAMs are potential candidates in the experimental treatments of disorders characterized by brain hypoperfusion, such as hypovolemic shock and cardiac arrest.